Online Multi-Appointment Scheduling Under Demand for Oncology Patient Treatment - Quezada-Valenzuela, F; Davila-Galvez, S; Fredes-Araya, M (Institute of Electrical and Electronics Engineers Inc., 2024)
This research is dedicated to formulating a practical problem related to the assignment of oncology clinic routes. The objective is to schedule medical events for patients attending health centers, taking into account the variable demand and limited resources in this field. To achieve this, three types of solutions are considered. The first is an Online Scheduling Algorithm, which simulates a scheduling process based on medical routes and also includes its inverse version. The next is a Mixed-Integer Linear Programming (MILP) model. In this case, information is centralized, and patients are scheduled based on their requirements, minimizing delays in their appointments and/or medical treatments. These methodologies are compared with the current mode of assignment used. To test the previously proposed solutions, data provided by the Arturo López Perez Foundation (FALP) will be used. © 2024 IEEE.